Fluid inclusion and isotopic constraints on the origin of ore‐forming fluid of the Jinman–Liancheng vein Cu deposit in the Lanping Basin, western Yunnan, China. Issue 1 (31st March 2015) - Song, Y.; Hou, Z.; Cheng, Y.; Yang, T.; Xue, C.
Abstract: Extensive quartz–carbonate–Cu sulfide veins occur in clastic rocks and are spatially related to Paleocene granites in the western border of the Lanping Basin, western Yunnan, China. Abundant aqueous‐carbonic fluid inclusions occur in these veins but their origin is debated. In the Jinman–Liancheng deposit, individual primary inclusion groups contain either exclusively liquid‐rich inclusions (Gl), or coexisting liquid‐rich and vapor‐rich inclusions (Glv). Microthermometry and estimate of CO2 content indicate that type Gl inclusions either have homogenization temperatures (Th) 238–263°C and contain c. 3.9–5.5 mole % CO2, or have Th 178–222°C and contain c. 1.6–3.2 mole % CO2 . Type Glv inclusions are thought to represent samples of fluid unmixing that occurred at 183–218°C. At that time, the liquid phase in the unmixing fluid may contain c. 2.0–3.3 mole % CO2 . As such, the correlation of CO2 content with Th for type Gl inclusions is thought to be caused by fluid unmixing with decreasing temperature and subsequent CO2 escape. δ 18 O and δD values of the parent water mainly fall in the field below that of primary magmatic water, indicative of fluid derivation from degassed (in open system) magmatic water, with no contributions from basinal or meteoric water. Initial Sr isotopic compositions of hydrothermal carbonates suggest that the fluid was magmatic, probably derived from the Paleogene granites. δ 13 CPDB values (−4‰ to −7‰) of the hydrothermal carbonates and δ 34 SV ‐ CDT values of sulfides (mainly −11‰ to +5‰) indicate that the carbon and sulfur can be derived from (degassed) magma and/or nonmagmatic sources. The CO2 ‐rich and magmatic‐water‐derived fluid at Jinman–Liancheng differs from the CO2 ‐poor and basinally derived fluid in sediment‐hosted stratiform Cu (SSC) deposits, which suggests that there are no genetic linkages between the vein Cu and SSC deposits in the Lanping Basin.